Therapeutic Potential of Human Amniotic Epithelial Cells on Injuries and Disorders in the Central Nervous System - Huiming Xu; Jiaofei Zhang; Kam Sze Tsang; Hao Yang; Wei-Qiang Gao (Hindawi Limited, 2019)
Despite recent advances in neurosurgery and pharmaceuticals, contemporary treatments are ineffective in restoring lost neurological functions in patients with injuries and disorders of the central nervous system (CNS). Therefore, novel and effective therapies are urgently needed. Recent studies have indicated that stem cells, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and mesenchymal stem cells (MSCs), could repair/replace damaged or degenerative neurons and improve functional recovery in both preclinical and clinical trials. However, there are many unanswered questions and unsolved issues regarding stem cell therapy in terms of potency, stability, oncogenicity, immune response, cell sources, and ethics. Currently, human amniotic epithelial cells (hAECs) derived from the amnion exhibit considerable advantages over other stem cells and have drawn much attention from researchers. hAECs are readily available, pose no ethical concerns, and have little risk of tumorigenicity and immunogenicity. Mounting evidence has shown that hAECs can promote neural cell survival and regeneration, repair affected neurons, and reestablish damaged neural connections. It is suggested that hAECs may be the most promising candidate for cell-based therapy of neurological diseases. In this review, we mainly focus on recent advances and potential applications of hAECs for treating various CNS injuries and neurodegenerative disorders. We also discuss current hurdles and challenges regarding hAEC therapies.